Art, Music, and Spectacle in the Age of Rubens: The Pompa Introitus Ferdinandi - Knaap, Anna C.; Putnam, Michael C. J. (Brepols Turnhout, 2013)
This volume deals with the triumphal entry of the Cardinal-Infante Ferdinand, brother of King Philip IV of Spain, into Antwerp in 1635, one of the largest and most spectacular festivals ever mounted in an early modern city. The outdoor festivities in honor of the city's new governor included a citywide procession, performances, fireworks, music, and political speeches. Along the processional route appeared nine richly ornamented stages and arches designed by Peter Paul Rubens and executed by a group of local painters and sculptors, including Jacob Jordaens, Theodoor van Thulden, and Jan van den Hoecke. To commemorate the event, the city commissioned a lavish festival book, entitled the Pompa Introitus Ferdinandi (1641), which contains learned commentaries by Jan Gaspar Gevaerts, a city official and Latinist, as well as folio engravings by Theodoor van Thulden after Rubens's stages. More than a simple description of the event, Gevaerts' volume offers a rich compilation of references to ancient writers and reproductions of ancient coins. While most literature on the subject has focused on Rubens's nine monumental arches and his twelve preparatory oil sketches for the designs, this volume will examine the entry and its accompanying festival book as a whole. A group of highly distinguished specialists from different disciplines will discuss the entry and Gevaerts' book from a myriad of viewpoints, including art, architecture, music, theater, history, politics, classical knowledge, and economic and intellectual networks. It is the first time that the entry will be examined from a truly interdisciplinary perspective. The book draws on a wide variety of primary sources, including Rubens's preparatory oil sketches, Gevaerts' festival book, pamphlets describing the entry, and political songs from the period.
Keywords: 17th Century (1601-1700); Fine art; Cultural history; Antwerp (Belgium)